2018
DOI: 10.1038/s41467-018-05753-w
|View full text |Cite
|
Sign up to set email alerts
|

Early selection of bZIP73 facilitated adaptation of japonica rice to cold climates

Abstract: Cold stress is a major factor limiting production and geographic distribution of rice (Oryza sativa). Although the growth range of japonica subspecies has expanded northward compared to modern wild rice (O. rufipogon), the molecular basis of the adaptation remains unclear. Here we report bZIP73, a bZIP transcription factor-coding gene with only one functional polymorphism (+511 G>A) between the two subspecies japonica and indica, may have facilitated japonica adaptation to cold climates. We show the japonica v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
170
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(177 citation statements)
references
References 72 publications
3
170
0
4
Order By: Relevance
“…We found that the expression level of AOX1a and AOX1b in ltt1 was more than 20 times higher than that in WT (Figure 4c). Because the activities of SODs and peroxidases appear to correlate positively with cold tolerance in rice (Kim, Choi, Cho, & Kim, ; Lee, Kwon, & Kim, ; Liu et al, ), we further detected the activity of the related enzymes in ltt1 and WT. The results showed that the activities of these enzymes in the mutant plants increased significantly (Figure 4d,e), which may help the mutant to eliminate the excessive ROS more effectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the expression level of AOX1a and AOX1b in ltt1 was more than 20 times higher than that in WT (Figure 4c). Because the activities of SODs and peroxidases appear to correlate positively with cold tolerance in rice (Kim, Choi, Cho, & Kim, ; Lee, Kwon, & Kim, ; Liu et al, ), we further detected the activity of the related enzymes in ltt1 and WT. The results showed that the activities of these enzymes in the mutant plants increased significantly (Figure 4d,e), which may help the mutant to eliminate the excessive ROS more effectively.…”
Section: Resultsmentioning
confidence: 99%
“…Although natural variation in CTB4a appears to enhance the tolerance of rice to cold stress (Zhang et al, ), some of the varieties with the most effective haplotype (Hap1), such as DAOHUAXIANG and DONGNONG428, are highly sensitive to cold stress during the booting stage. Similarly, bZIP73 was identified as a QTL for seedling chilling tolerance (Liu et al, ), and the function of this gene on cold tolerance at the booting stage could only be observed in transgenic lines (Liu et al, ). In view of the severe damage of booting stage cold stress on rice yield and the functional uncertainties of the currently reported cold tolerance genes, there is an urgent need to provide effective cold tolerant genetic resources for traditional breeding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, determination of chilling tolerance in rice at seedling stage uses the survival rates of rice seedlings after chilling treatment as the primary indicator (Ma et al 2015; Lv et al 2017; Zhang et al 2017b; Liu et al 2018a; Mao et al 2019). Identification of chilling tolerance at booting stage is typically determined based on yield traits such as seed setting rates and relative seed setting rates, together with pollen fertility (Zhang et al 2017b; Liu et al 2019).…”
Section: The Influence Of Chilling Stress On Ricementioning
confidence: 99%
“…Given its tropical origin, cultivated rice germplasm genetic variability is very limited to identify cold stress tolerance genes and alleles (Byun et al 2017). A few examples of alleles associated with low temperature tolerance are derived from japonica subspecies, as COLD1 jap and bZIP73 jap (Ma et al 2015; Liu et al 2018). Indeed, transferring the japonica alleles to indica rice genotypes increased its cold tolerance.…”
Section: Introductionmentioning
confidence: 99%